Maximum-energy records in glassy energy landscapes. (11th September 2019) - Hartarsky, Ivailo; Baity-Jesi, Marco; Ravasio, Riccardo; Billoire, Alain; Biroli, Giulio
Abstract: We study the evolution of the maximum energy reached between time 0 and time t in the dynamics of simple models with glassy energy landscapes, after an instant quench from infinite temperature to a target temperature T. Through a detailed description of the activated dynamics, we are able to describe the evolution of from short times, through the aging regime, until after equilibrium is reached, thus providing a detailed description of the long-time dynamics. Finally, we compare our findings with numerical simulations of the p-spin glass and show how the maximum energy record can be used to identify the threshold energy in this model.